(NfIZIKA UDARNYH WOLN W GAZAH I PLAZME (B/s - (NwELIKOWI^(B, (NaLEKSANDR lAZAREWI^s; (NlIBERMAN(B, (NmIHAIL aNDREEWI^s; (NzELXDOWI^(B, (Nq(B.(Nb(B.s; (NiNSTITUT FIZI^ESKIH PROBLEM IM(B. (Ns(B.(Ni(B. (NwAWILOWAs ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 286-291 (147 (NNAZW(B.)s
Keywords: (NtEORETI^ESKAQ HIMIQs